Hybrid control strategies of SVC for reactive power compensation - Mothanna Sh. Aziz; Ahmed G. Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This article shows a prospective utilizations of flexible AC transmission system (FACTS) controls, like the static VAR compensator (SVC). One of the major motives for setting up an SVC is to recover dynamic voltage controller and thus increase system load aptitude. Static VAR compensator system proposed in this work consists of thyristor switched capacitor and thyristor controlled reactor sets, this style of SVC modelled using MATLAB simulink toolbox. A hybrid genetic algorithm with PI and fuzzy logic controls that used to control and expand the grid performance of the power system. The model results reveal that the Static Var Compensation contribute a decent result in upholding bus voltage after the power network is in an active and steady moment, besides it has a capability of the constancy control. It can totally work as a significant plan of reactive power recompense in power networks.